Réponses

2014-09-14T14:58:22+02:00
A) 4x+8 = 4*x+4*2     ( Facteur commun : 4 )
       
     = 4*(x+2)

b) a²-15a = a*a-15*a     ( Facteur commun : a )
             
  = a*(a-15)

c) 7y-7 = 7*y-7*1    ( Facteur commun : 7 )
            =
7*(y-1)

d) 4a²-6ab+10a = 2a*2a+2a*(-3b)+2a*5  ( Facteur commun : 2a )
                       
  = 2a*(2a-3b+5)

e) (a+5)(2a+3)+(a+5)(3a-5)     ( Facteur commun : a+5 )
 = (a+5)*(2a+3+3a-5)
 = (a+5)*(5a-2)

f) (3b+2)(3b-2)+(5b)(3b-2)     ( Facteur commun : 3b-2 )
= (3b-2)*(3b+2+5b)
= (3b-2)*(8b+2)